2015
DOI: 10.1155/2015/247531
|View full text |Cite
|
Sign up to set email alerts
|

Study of Aerosols’ Characteristics and Dynamics over the Kingdom of Saudi Arabia Using a Multisensor Approach Combined with Ground Observations

Abstract: This study covers various aspects of the aerosol distribution and characteristics, namely, optical depth climatology, absorption characteristics, and their microphysical properties over four regions in Saudi Arabia using satellite and ground observations including MODIS/Terra and Aqua, OMI, MISR/Terra, AERONET, and CALIPSO for the period April 2003–January 2013. The study includes cities in the North Western, Western, Eastern provinces of Saudi Arabia and in the Rub al Khali desert or Empty Quarter. Satellite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Alharbi et al (2013) reported that the AOD is unexpectedly increased over Dhahran is of an exceptionally high level as a result of frequent sand and dust events, in addition to the industrial activities in that region. Moreover, it has been related by Farahat et al (2015) based on MODIS DB AOD at 550 nm data, that the AOD levels peak during spring season over the Rub Al Khali desert due to the frequent dust events. The authors also used OMI data to highlight excessive levels of air contamination over Dhahran.…”
Section: Spatial Distribution Of Seasonal Mean Aodmentioning
confidence: 99%
See 1 more Smart Citation
“…Alharbi et al (2013) reported that the AOD is unexpectedly increased over Dhahran is of an exceptionally high level as a result of frequent sand and dust events, in addition to the industrial activities in that region. Moreover, it has been related by Farahat et al (2015) based on MODIS DB AOD at 550 nm data, that the AOD levels peak during spring season over the Rub Al Khali desert due to the frequent dust events. The authors also used OMI data to highlight excessive levels of air contamination over Dhahran.…”
Section: Spatial Distribution Of Seasonal Mean Aodmentioning
confidence: 99%
“…There are limited studies available on satellite based AOD over Saudi Arabia. For example, the AOD climatology based on the satellite remote sensing data has been studied over different Provinces of Saudi Arabia (Farahat et al, 2015). Sabbah and Hasan (2008) studied the ground-based measurements of aerosol optical depth over the Solar Village, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Rub' al Khali (Empty Quarter) sand desert is a major source of frequent dust outbreaks and 32 severe dust storms that has major effect on human activity in the Arabian Peninsula (Böer, 33 1997, Elagib and Addin 1997, Farahat et al, 2015. 34…”
Section: Introduction 28mentioning
confidence: 99%
“…Optical techniques are used to estimate particle sizes; however, determining particle types requires more information regarding aerosol sources, trajectories, regional topography, and atmospheric conditions. As for radiative impacts, aerosol characterization and types are major input parameters for obtaining precise climate predictions (Ramanathan et al, 1989;Satheesh and Moorthy, 2005;Farahat et al, 2015). For instance, particle absorption characteristics are used in assessing aerosol emission sources, types, and interaction phases .…”
Section: Introductionmentioning
confidence: 99%